IFA inside out - Pasel, Ralf (CODE / architectural files, 2022)
INSIDE OUT is a design build experiment that merges curatorial practice in an interactive installation as part of the IFA annual exhibition 2021 at the Institute for Architecture in the Hermkes Building on Ernst Reuter Platz in Berlin. Shaped by the events of the Covi-19 pandemic, the question of the exhibition concept at a distance plays the central role that decides on production, design and implementation.